Variable thermal conductivity effects on MHD flow of non-Newtonian ternary hybrid nanofluid between rotating disks, A Cattaneo–Christov heat transfer analysis - Hussan Zeb; Kamal Shah; Manar Alqudah; Thabet Abdeljawad (Case Studies in Thermal Engineering)
This work has been motivated by the increasing need for fluid flow optimization and advanced thermal management systems in engineering applications that demand superior heat transfer characteristics. The study examines the casson fluid and thermal dynamics of ternary hybrid nanofluids, which are composed of up of Cobalt Firrite CoFe2O3 aluminum oxide Al2O3 and titanium-oxide (TiO2) in a water-based fluid that flows between two rotating disks. The impacts of mixed convection, magnetic fields, and quadratic thermal radiation are all taken into account. This work offers essential findings for boosting efficiency in energy systems, electronics cooling, and magnetic fluid technologies by filling in knowledge gaps in viscoelastic fluid dynamics, magnetic influences, and sophisticated heat transfer mechanisms. Furthermore, Cobalt Firrite CoFe2O3 aluminum oxide Al2O3 and titanium-oxide (TiO2) are ternary hybrid nanofluids that function well in applications like energy-efficient heat exchangers, magnetic fluid-based technologies, and advanced electronic cooling systems where boosted thermal conductivity and fluid dynamics are needed. The Cattaneo–Christov model is used to study heat transmission, taking into account heat sources, viscous dissipation, and thermal relaxation. In advanced engineering applications, findings aim to help in developing of more efficient heat management technologies. The governing nonlinear partial differential equations are converted into dimensionless form by using the Von Karman transformations. To fined the solution numerically by the combining shooting techniques with the Runge–Kutta method. The analysis investigates how the axial and radial velocity profiles, as well as the fluid’s temperature distribution, are affected by important parameters such the Reynolds number, rotational parameters, magnetic field strength, and momentum slip. The findings show that, in comparison to combinations of simple , hybrid nanoparticles and the presence of ternary hybrid nanoparticles greatly improves heat transfer efficiency, particularly at higher Reynolds numbers and rotation rates. Furthermore, the model improves heat exchanger performance, boosts the efficiency of solar energy that use nanoparticles, and helps optimize fluid flow in medical applications.